Evaluation of native bacteria and manganese phosphite for alternative control of charcoal root rot of soybean - Simonetti, Ester (2015)
Plant growth promoting rhizobacteria (PGPR) are potential agents to control plant pathogens and their combined use with biopesticides such as phosphites may constitute a novel strategy to incorporate in disease management programs. In the present study, 11 bacterial isolates were selected on the basis of their antagonistic activity against Macrophomina phaseolina in dual-culture tests, and their plant growth promoting traits. Selected isolates were characterised on the basis of auxin and siderophore production, phosphate solubilisation and rep-PCR genomic fingerprinting. Two of these isolates, identified as Pseudomonas fluorescens 9 and Bacillus subtilis 54, were further evaluated for their inhibitory capacity against M. phaseolina using in vitro (on soybean seeds) and in vivo (greenhouse assay) tests. Both bacteria were applied individually as well as in combined treatment with manganese phosphite as seed treatments. Damage severity on soybean seeds was significantly reduced, compared with the untreated control, by both bacterial strains; however, the individual application of phosphite showed to be least effective in controlling M. phaseolina. Interestingly, the phosphite treatment improved its performance under greenhouse conditions compared to the results from the in vitro assays. In the greenhouse trials, the greatest reductions in disease severity were achieved when strain P. fluorescens 9 was applied singly or when strain B. subtilis 54 was combined with manganese phosphite, achieving 82% of control in both cases. This work is the first to report the control of M. phaseolina using combined treatment with PGPR and phosphite under greenhouse conditions.